English Teachers-Principle Interaction in English Teachers Social at SMA Negeri 1 Tuhemberua - Peristiwa Diken Kasatria Zai; Hidayati Daeli; Yaredi Waruwu; Riswan Zega (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to analyze the social interaction between English teachers and the principal in the implementation of the Subject Teachers’ Meeting (MGMP) and its impact on teacher professional development. The research was conducted at SMA Negeri 1 Tuhemberua, North Nias Regency, from January to March 2025. The population of this study consisted of the school principal and English teachers who actively participated in MGMP activities, and all participants were involved as research subjects. This study employed a qualitative descriptive approach with a field research design. Data were collected through observation, semi-structured interviews, questionnaires, and documentation. The data analysis technique used was qualitative inductive analysis, which included data reduction, data display, and conclusion drawing, supported by triangulation to ensure data validity. The results indicate that social interaction between English teachers and the principal occurred through several forms, namely supervision, coordination, collaboration, facilitation, and motivation. These interactions generally functioned well and contributed positively to teacher professionalism, work motivation, and the implementation of instructional innovations in English language learning. However, several obstacles were identified, including limited time availability of the principal, insufficient facilities and budget support, and the absence of formal reward mechanisms for active teacher participation in MGMP activities. Despite these constraints, the interaction within the MGMP had a positive impact on strengthening teacher collaboration, improving instructional practices, and enhancing the quality of learning at school. This study is expected to contribute theoretically to studies on educational leadership and teacher professional communities, as well as practically to schools in optimizing the role of principals and MGMP as effective platforms for teacher professional development.